Book Reviews - Paul Brunton; Janet Howse; Ron Gilchrist; John Thompson; H. J. Gibbney (Archives & Manuscripts, 1983)
Our heritage: a directory to archives and manuscript repositories in Australia reviewed by Paul Brunton; Guidelines on establishing a microfilming programme, and Microfilming of records reviewed by Janet Howse; Removal of a records centre and its contents reviewed by Ron Gilchrist; Dear Robertson: Letters to an Australian publisher reviewed by John Thompson; Tracing your ancestors: a guide to genealogical sources in the J.S. Battye Library of West Australian History reviewed by H. J. Gibbney